MARKETING ASPECTS OF DEVELOPING A COMPETITIVE STRATEGY FOR A COMPANY AND ASSESSING ITS COMPETITIVENESS - SAVCHENKO, tetiana; BURYACHENKO, Yuriy; KRYVENOK, Andrii; KRULIKOVSKY, Kostyantyn (Herald of Khmelnytskyi National University. Economic sciences, 2024)
The article examines the stages of developing a company's competitive strategy and establishing its competitiveness. Factors affecting the establishment of the company's competitiveness are characterized: globalization of markets, rapid technological changes, constant change in consumer preferences, competition in the industry, growing importance of marketing. Theoretical approaches to the definition of types of competition, such as behavioral, structural and functional approaches, are considered. Factors and initial data influencing the formation of the company's competitive strategy have been established. The formation of the company's competitive strategy is impossible without the analysis of external and internal factors of the company's marketing environment, this process involves the definition and comparative characteristics of factors that have both positive and negative effects on the company's environment. The proposed structural-logical scheme for determining the company's competitive strategy. The formation of the company's competitive strategy is considered according to the stages of strategic planning. The competitive strategy of the enterprise is a set of competitive strategies, which differ among themselves in the breadth of coverage of management decisions, the level of responsibility and the stage of strategic planning at which a certain competitive strategy is formed.The first level is corporate strategy: it is determined based on the analysis of competitive positions or the economic state of the enterprise. The second level is business strategy: this strategy involves the development of measures aimed at strengthening competitiveness and preserving competitive advantages; formation of a response mechanism to external changes, etc. The third level is the functional strategy (business level): taking into account the general level of competitiveness of the enterprise, the competitive positions of individual business divisions are determined. The fourth level - operational strategy: focuses on specific strategic initiatives and approaches to the management of key operational units when solving daily operational tasks that have strategic importance, the competitiveness of individual products is determined.The methodological apparatus used at individual stages of assessing the competitiveness of the enterprise and determining its competitive strategy is characterized.
Keywords: enterprise competitiveness; competitive positions; competitive strategy; marketing research; marketing environment; evaluation methods